Seeing things politically: interviews with Bénédicte Delorme-Montini - Manent, Pierre (St. Augustine's Press, 2015)
"These autobiographical and philosophical essays, in the form of expertly probing interviews, provide a superb introduction to the work of one of the most significant contemporary political philosophers and a marvelously readable perspective on the French intellectual and political arenas from the 1970s to the present. Those already familiar with Manent's work will find an indispensable reflection on his transition from the critique of modernity brilliantly represented in his earlier books (most notably Tocqueville and the Nature of Democracy and The City of Man), a critique at once original and significantly indebted to Leo Strauss, toward a perspective that emerges in his recent The Metamorphoses of the City, a monumental and profoundly original study that endeavors to situate modernity within the original Greek founding of the act of politics. The autobiographical passages in this vivid and engaging work invite the reader into, first, the world of postwar France in which Manent grew up, in which he was presented with the choice between the Communist hopes of his father and the opposing power and prestige of all things American. There is also an impressive portrait of the rigors and spirit of a provincial lycee where the first sparks of philosophical eros ignited in Manent's soul, and of his studies in the legendary Ecole Normale Superieur in the midst of the ideological confusion associated with the ferment of 1968. The reader then is invited to an inside view of the rise of a broadly Tocquevillean school of French thought around the journal Contrepoints and its successor Commentaire"--